2020
DOI: 10.1002/ejoc.202000673
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed One‐Pot Synthesis of 3‐(N‐Heteroarenyl)acrylonitriles through Radical Conjugated Addition of β‐Nitrostyrene to Methylazaarenes

Abstract: A simple procedure for the copper‐catalyzed synthesis of 3‐(N‐heteroaryl)acrylonitriles was developed. Using a combination of Lewis and Brønsted acids, this one‐pot procedure undergoes via a radical conjugated addition and dehydration processes, without isolation of any intermediate, affording the acrylonitriles. This diastereoselective approach allowed the synthesis of a broad scope of quinazoline derivatives (22 examples) with moderate to good yields and good functional‐group tolerance and could be extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We began our studies with the optimization of the reaction conditions, using trans -β-methyl-β-nitrostyrene ( 1a ) and 4-methylquinazoline 2a as model substrates. Based on our previous reports, we initially used CuI (10 mol %) and HCl 0.5 M (10 mol %) in N , N -dimethylformamide (DMF), in which the desired product 3a was obtained in 54% yield (Table , entry 1). Then, we performed a screening of solvents using CuI as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We began our studies with the optimization of the reaction conditions, using trans -β-methyl-β-nitrostyrene ( 1a ) and 4-methylquinazoline 2a as model substrates. Based on our previous reports, we initially used CuI (10 mol %) and HCl 0.5 M (10 mol %) in N , N -dimethylformamide (DMF), in which the desired product 3a was obtained in 54% yield (Table , entry 1). Then, we performed a screening of solvents using CuI as a catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the 1,4-addition of nitroolefins to 4-methylquinazolines was found to occur through a radical mechanism . In order to contribute with the mechanism pathway of this new method, we performed the reaction between trans -β-methyl-β-nitrostyrene ( 1a ) and 4-methylquinazoline ( 2a ) in the presence of (2,2,6,6-tetramethylpiperidin-1-yl)­oxyl (TEMPO) (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation